2015
DOI: 10.3354/ame01763
|View full text |Cite
|
Sign up to set email alerts
|

Top-down control by micro- and mesozooplankton on winter dinoflagellate blooms of Heterocapsa rotundata

Abstract: Winter dinoflagellate blooms in Chesapeake Bay tributaries can account for over 50% of a system's annual primary production, potentially more than the spring diatom bloom. Research on winter blooms has focused on environmental conditions that result in blooms, but little focus has been given to the potential importance of zooplankton grazers. We investigated the impact of microzooplankton and mesozooplankton (copepods) grazing on the population of winter phytoflagellates in the Choptank River, MD, in 2012 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Recent analysis of long-term changes in phytoplankton community composition over this same timeframe have suggested that dinoflagellates have become an increasing portion of phytoplankton biomass, whereas previously the composition was dominated by diatoms (Harding et al, 2015b). Winter blooms of dinoflagellates have been documented in the estuarine turbidity maximum region of the main stem Chesapeake Bay, in the vicinity of the CB3.1 (Lee et al, 2012), as well as in multiple tributaries of Chesapeake Bay (Sellner et al, 1991;Millette et al, 2015). Many of these species tend to be mixotrophic, using phagotrophy as an alternative energy acquisition strategy during winter-spring in turbid waters, where low light availability limits photoautotrophy (Millette et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of long-term changes in phytoplankton community composition over this same timeframe have suggested that dinoflagellates have become an increasing portion of phytoplankton biomass, whereas previously the composition was dominated by diatoms (Harding et al, 2015b). Winter blooms of dinoflagellates have been documented in the estuarine turbidity maximum region of the main stem Chesapeake Bay, in the vicinity of the CB3.1 (Lee et al, 2012), as well as in multiple tributaries of Chesapeake Bay (Sellner et al, 1991;Millette et al, 2015). Many of these species tend to be mixotrophic, using phagotrophy as an alternative energy acquisition strategy during winter-spring in turbid waters, where low light availability limits photoautotrophy (Millette et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…). At this location H. rotundata is known to dominate the winter phytoplankton community and form large winter blooms (Millette et al ). On each sampling date we collected 10 L of surface water with a bucket, and immediately filtered it through 20 μm mesh to remove larger plankton.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have focused on the formation and decline of H. rotundata winter blooms in Chesapeake Bay tributaries (Cohen ; Sellner et al ; Millette et al ). These researchers found abundant H. rotundata blooms in wet, cold winters when salinity is low (Cohen ) and when there is a release in grazing pressure from microzooplankton and copepods (Millette et al ). Although wet, cold winters and a release in grazing pressure are factors that impact every phytoplankton species, it is unknown how H. rotundata can take advantage of these conditions over other species to bloom.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic photoinhibition and swelling of Heterocapsa rotundata even in moderate irradiances, coupled with its high photosynthetic efficiency at low irradiances, suggests a bloom niche characterized by very low light. In Chesapeake Bay, Heterocapsa rotundata often blooms in winter when light limits the growth of other phytoplankton and predators are scarce as a result (Cohen 1985, Sellner et al 1991, Millette et al 2015. By up-regulating feeding in response to low light (Millette et al 2017) and, as shown here, by optimizing photosynthetic performance under these conditions, H. rotundata appears to gain an advantage over other phytoplankton.…”
Section: Discussionmentioning
confidence: 51%